1997
DOI: 10.1007/s004649900336
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic salvage of malfunctioning peritoneal catheters

Abstract: Laparoscopic revision is a successful technique for salvage of occluded peritoneal catheters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 9 publications
3
35
1
Order By: Relevance
“…The documented complications include peritonitis, tunnel infections, dialysate leaks, hernias, and hemorrhages (10)(11)(12)(13)(14). In addition, due to the peritoneal punctures, PD may have to be discontinued for a few weeks after laparoscopic surgery and this often requires a temporary transition to hemodialysis while the incisions heal.…”
Section: Discussionmentioning
confidence: 99%
“…The documented complications include peritonitis, tunnel infections, dialysate leaks, hernias, and hemorrhages (10)(11)(12)(13)(14). In addition, due to the peritoneal punctures, PD may have to be discontinued for a few weeks after laparoscopic surgery and this often requires a temporary transition to hemodialysis while the incisions heal.…”
Section: Discussionmentioning
confidence: 99%
“…Amerling et al [17] reported that the success rate of laparoscopic salvage of malfunctioning peritoneal catheters was 93%. Previously reported success rates of laparoscopic surgery were greater than 80% [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Our published reports of over 400 buried PD catheters have shown that this technique is associated with low rates of surgical, mechanical, and infectious complications (3). Over the years, we have noted from time to time asymptomatic peritoneal leukocytosis with negative effluent cultures immediately after exteriorization of a buried catheter.…”
Section: Disclosuresmentioning
confidence: 80%